Effect of Trap Depth and Interfacial Energy Barrier on Charge Transport in Inverted Organic Solar Cells Employing Nanostructured ZnO as Lectron Buffer Layer - Rajan, Jose; Elumalai, Naveen Kumar; Ramakrishna, Seeram; Vijila, Chellappan; Jie, Zhang (Inderscience Enterprises Ltd., 2014)
Inverted organic solar cells withdevice structure ITO/ZnO/poly (3-hexylthiophene) (P3HT):[6,6]-phenyl C61 butyric acid methyl ester (PCBM)/ MoO3/Ag were fabricated employing low temperature solution processed ZnO as electron selective layer. Devices with varying film thickness of ZnO interlayer were investigated. The optimum film thickness was determined from photovoltaic parameters obtained from current-voltage measurements. Furthermore, the distribution of localised energy states or trap depth and the ohmicity of the contacts in the optimised device were evaluated, using the temperature and illumination intensity dependent study. The results demonstrate the effect of trap depth distribution on the charge transport, device performance, and stability of the contacts.